THE DESIGN OF INFORMATION SYSTEM FOR CAD DIVISION IN GARMENT FIELD WITH WATERFALL METHOD - Agung Alan (Jurnal Riset Sistem Informasi dan Teknologi Informasi (JURSISTEKNI), 2021)
Sukabumi Regency has various industrial or garment companies scattered in several regions. One of them is PT. Yongjin Javasuka Garment, which is located in the cicurug sub-district, can support the economic pace of local residents by opening jobs as laborers. In the world of garment, there are many organizations that are active in every field. The CAD is a division that works as a support role to launch a production process from start to finish. For his work in this division, he has a lot of expertise and several different sections, namely an adm, pattern maker, marker, plot pattern and plot marker. When working, everything interacts and relates to each other. Through the internet, all computers can access each other's data. However, in practice now there are still obstacles that should be evaluated jointly. Data provided from one employee to another is still manual. This causes the work to be less effective, slow and thus not optimal. In the above case, we need an information system that can accommodate data with internet services to maximize the company's facilities. Easy, fast and integrated information system. Therefore, in this study, the waterfall method is used to make it easier for employees while working in accessing data.